Enhanced growth and nutrient uptake of Pterocarpus indicus in asphalt post-mining soil media using local arbuscular mycorrhizal fungi - HUSNA HUSNA; FAISAL DANU TUHETERU; WIWIN RAHMAWATI NURDIN; RAMADIN RAMADIN; ASRIANTI ARIF (Society for Indonesian Biodiversity, 2025)
Abstract. Husna, Tuheteru FD, Nurdin WR, Ramadin, Arif A. 2025. Enhanced growth and nutrient uptake of Pterocarpus indicus in asphalt post-mining soil media using local arbuscular mycorrhizal fungi. Biodiversitas 26: 1956-1963. Local Arbuscular Mycorrhizal Fungi (AMF) were previously reported to be effective in increasing the growth and nutrient uptake of legume plant in various degraded soil media, such as serpentine, coal spoil, and tailings. The entire previous studies related to AMF were not conducted in asphalt post-mining soil media. Therefore, this study aimed to examine the effect of local AMF inoculation on the growth and nutrient uptake of Pterocarpus indicus in asphalt post-mining soil media under Indonesian Mycorrhizal Association nursery conditions. A total of 7 treatments were tested in a 3-month experimental period by using seedlings of P. indicus. These included (A) control (no inoculation), as well as soil media inoculated with (B) Glomus coronatum, (C) Glomus claroideum, (D) Glomus halonatum, (E) mixed AMF (G. claroideum + G. coronatum), (F) mixed AMF (G. claroideum + G. halonatum), and (G) mixed AMF (G. coronatum + G. claroideum + G. halonatum). The parameters observed were AMF colonization percentage, nutrient content, plant growth, as well as the uptake of N, P, K, and Zn. After 3 months of experiment, the AMF colonization percentage in P. indicus ranged between 55.00% and 69.33%. G. claroideum and G. coronatum colonization showed higher plant growth in terms of height, diameter, number of leaves, and nodules, dry weight, as well as N, P, K, and Zn content at nursery conditions. P. indicus and mixed AMF consisting of G. claroideum and G. coronatum can be used for the restoration program in asphalt post-mining land in the tropics.